Robot-assisted flexible ureteroscopy: an update - Rassweiler, Jens; Fiedler, Marcel; Charalampogiannis, Nikolaos (Urolithiasis, 2018)
The role of flexible ureteroscopy (FURS) in the management of nephrolithiasis has increased due to the improved armamentarium. However, FURS still represents a challenging technique limiting its diffusion. Similar to previous experiences in laparoscopy, recently developed robotic devices may significantly compensate for the ergonomic deficiencies of FURS. Based on a short description of the history of robotic devices for laparoscopy, this article summarizes all current developments of robotic FURS. In 2008, robotic FURS was first reported using the Sensei-Magellan system designed for interventional cardiology. However, with this device the ureteroscope was only passively manipulated, which represented the main reason why this project has been discontinued after 18 clinical cases. Avicenna Roboflex™ was especially developed for FURS. It consists of a surgeon’s console and manipulator of a flexible ureterorenoscope. The console provides an adjustable seat with armrests and two manipulators of the endoscope: the right wheel enables deflection and the left horizontal joystick allows rotation as well as advancing and retracting the instrument. The speed of rotation and advancement can be regulated at the screen of the console. Using the IDEAL system for evaluation of new robotic devices, safety and efficacy of the system could be demonstrated in two multi-centric studies providing significant improved ergonomics for the surgeon (IDEAL stage 1 and 2). Future studies are necessary to determine the final role of robotic FURS.